Determination of the solubility of rivaroxaban (anticoagulant drug, for the treatment and prevention of blood clotting) in supercritical carbon dioxide: Experimental data and correlations - Gholamhossein Sodeifian; Mohammad Mahdi Behvand Usefi; Fariba Razmimanesh; Armin Roshanghias (Arabian Journal of Chemistry, 2023)
Supercritical processes are utilized in pharmaceutical, chemical, agricultural and food industries. To design the micro or nanoparticles formation processes via a supercritical fluid (SCF), it is necessary to have available the solubility data of a solid solute in a solvent such as supercritical carbon dioxide (SC-CO2). In this article, the solubility of rivaroxaban (anticoagulant drug, for the treatment and prevention of blood clotting) in SC-CO2 was investigated for the first time. Six semi-empirical models (Chrastil, Bartle, Jouyban, Garlapati and Madras, and Sodeifian) and two equation of states (EoSs) including Peng-Robinson (PR) and Soave-Redlich-Kwong (SRK) with twin-parametric van der Waals (vdW2) and covolume dependent (CVD) mixing rules were used to examine the correlation of drug solubility data. The best performance was obtained by semi-empirical Jouyban model (Average absolute relative deviation (AARD = 12.436 %)) and PR-vdW2 EoS (AARD = 5.104 %). Total and vaporization enthalpies were calculated 43.617 KJ.mol−1 and 63.288 KJ.mol−1, respectively.